2021
DOI: 10.1002/jbt.22858
|View full text |Cite
|
Sign up to set email alerts
|

In vitro therapeutic effects of abemaciclib on triple‐negative breast cancer cells

Abstract: The cyclin-dependent kinases 4 and 6 have led to a significant improvement in the treatment of hormone-receptor-positive breast cancer. However, the therapeutic potential of abemaciclib in triple-negative breast cancer (TNBC) has not been definitively elucidated. Therefore, the objective of this study was to investigate abemaciclib mediated antiproliferative effects on MDA-MB-231 and MDA-MB-468 TNBC and MCF-10A cell line through annexin V, cell cycle, caspase-3, reverse transcription-polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Doxo is a widely used chemotherapeutic agent that exerts anticancer effects and induces cellular senescence in different cell types and mouse models [54][55][56][57][58][59] . Abe causes cell cycle arrest and reduces cell proliferation by inhibiting CDK4/6, thereby contributing to senescence [60][61][62] . Stable cellular senescence was induced in MDA-MB-231 and MCF-7 cells using Doxo and Abe.…”
Section: Discussionmentioning
confidence: 99%
“…Doxo is a widely used chemotherapeutic agent that exerts anticancer effects and induces cellular senescence in different cell types and mouse models [54][55][56][57][58][59] . Abe causes cell cycle arrest and reduces cell proliferation by inhibiting CDK4/6, thereby contributing to senescence [60][61][62] . Stable cellular senescence was induced in MDA-MB-231 and MCF-7 cells using Doxo and Abe.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sekeroglu et al demonstrated that abemaciclib caused significant apoptosis in TNBC cells via G0/G1 arrest, chromatin condensation, the upregulation of caspase-3 and Bax levels, and the downregulation of Bcl-2. The formation of a large number of cytoplasmic vacuoles not associated with autophagy suggested that treatment with 16 could be effective for TNBC [92] (Figure 3).…”
Section: Abemaciclib (16)mentioning
confidence: 99%
“…Extensive preclinical research has validated the mechanisms by which CDK4/6 inhibition promotes CD8 T cell memory formation, regulates PD‐L1 protein expression, and alters the tumor immune microenvironment 13 . Preliminary studies by Ozman et al 14 . and Peng et al 15 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Extensive preclinical research has validated the mechanisms by which CDK4/6 inhibition promotes CD8 T cell memory formation, regulates PD-L1 protein expression, and alters the tumor immune microenvironment. 13 Preliminary studies by Ozman et al 14 and Peng et al 15 have also identified the potential antitumor effects of abemaciclib in triplenegative breast cancer (TNBC). Two ongoing clinical trials (NCT03979508 and NCT01042379) are recruiting TNBC patients for investigation involving abemaciclib.…”
Section: Introductionmentioning
confidence: 99%